A Qualitative Research Synthesis of the "No Excuses" Charter School Model. Issue 5 (July 2022) - Ellison, B. Scott; Iqtadar, S.
The "no excuses" charter school model is widely regarded in public debate as an effective policy intervention to politically and economically empower historically marginalized student populations. The organizing principle of the "no excuses" model is to do whatever it takes to close the achievement gap and to prepare students for university education and the professional job market. This article seeks to critically evaluate the "no excuses" model through a qualitative research synthesis of an emerging body of qualitative research literature. The findings from this synthesis raise serious questions about the desirability of the "no excuses" charter school model.